Shilajit‐induced potentiation of the hypoglycaemic action of insulin and inhibition of streptozotocin induced diabetes in rat - Kanikkannan N.; Ramarao P.; Ghosal S. (My University, 2025)
The effects of subcutaneous (s.c.) administration of processed shilajit (PS) alone and in combination with insulin (s.c.) on plasma glucose levels (PGL) were determined in either sex of streptozotocin‐induced diabetic (SID) rats. PS (50 μ/kg; s.c.) did not alter plasma glucose levels in SID rats. Insulin (0.25‐1.0 U/kg; s.c.), dose‐dependently produced hypoglycaemia in SID rats. PS (50 μg/kg; s.c.) potentiated and prolonged the hypoglycaemic action of insulin when administered concurrently. Chronic administration of PS (0.1–10 mg/kg; b.i.d. for 10 days; i.p.) had no influence per se on plasma glucose levels. Chronic administration of PS (1.0 mg/kg; b.i.d. for 10 days; i.p.) prevented the streptozotocin (STZ)‐induced diabetes in rats, whereas a relatively lower (0.1 mg/kg; b.i.d. for 10 days; i.p.) and significantly higher dose (10 mg/kg; b.i.d. for 10 days; i.p.) of PS had no influence on the STZ‐induced diabetes. The results suggest that administration of PS along with insulin would potentiate the insulin‐induced hypoglycaemia, and chronic administration of a carefully determined dose of PS would inhibit the development of STZ‐induced diabetes. Copyright © 1995 John Wiley & Sons, Ltd.